2018
DOI: 10.1159/000489115
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Auditory Forebrain Responses to Non-Learned Vocalizations in Juvenile Blackbirds

Abstract: Species recognition mediates the association of individuals with conspecifics. Learned cues often facilitate species recognition via early social experience with parents and siblings. Yet, in some songbirds, the production of species-typical vocalizations develops in the absence of early social experiences. Here, we investigate the auditory-evoked neural responses of juvenile red-winged blackbirds (Agelaius phoeniceus), a nonparasitic (parental) species within the Icterid family and contrast these results with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
2
7
1
Order By: Relevance
“…Taken together, these results support a model of neural activation to represent stimulus‐dependent neural selectivity of specific content of the playback types (e.g. conspecific versus heterospecific), rather than the acoustic contrasts between stimulus sounds (Lynch et al , ).…”
Section: Neural Responses To Species‐specific Soundssupporting
confidence: 71%
See 3 more Smart Citations
“…Taken together, these results support a model of neural activation to represent stimulus‐dependent neural selectivity of specific content of the playback types (e.g. conspecific versus heterospecific), rather than the acoustic contrasts between stimulus sounds (Lynch et al , ).…”
Section: Neural Responses To Species‐specific Soundssupporting
confidence: 71%
“…Thus, neural response selectivity could depend purely on the acoustic dis/similarities between conspecific and heterospecific sounds used as stimuli (Mendelson et al, 2016). However, IEG activation in red-winged blackbirds (Agelaius phoeniceus) did not reflect acoustic similarities between the call used as the conspecific stimulus versus heterospecific stimulus calls of two different species (Lynch, Louder, & Hauber, 2018). Similarly, Hauber et al (2013) found the neural firing rates of zebra finches responded at similarly lower levels to the heterospecific songs of Bengalese finch (Lonchura striata domestica) and Parson's finch (Poephila cincta) versus conspecific songs, and Poirier et al (2009) found greater neural responses in zebra finches upon hearing conspecific songs versus multiple exemplars of canary (Serinus canaria domestica) and European starling (Sturnus vulgaris) songs, despite the contrasting acoustic structures of each set of heterospecific stimuli.…”
Section: (2) Species-specific Stimulimentioning
confidence: 98%
See 2 more Smart Citations
“…What constitutes the physiological basis of anti-parasite responses remains largely unknown in avian host-parasite systems 10 . For example, recent work in wild-caught juvenile male red-winged blackbirds (Agelaius phoeniceus; hereafter: redwings) found no differences in immediate early gene (IEG) expression levels within the auditory forebrain in response to the calls of adult female brood parasites (brown-headed cowbirds Molothrus ater; hereafter: cowbirds) versus a harmless control species (mourning dove Zenaida macroura; hereafter: doves), whereas responses were stronger to conspecific adult female calls 11 . In the wild, however, juvenile redwings do not hold territories and may not (yet) have been exposed to parasitism by cowbirds.…”
mentioning
confidence: 99%